Conversion Option on the Implementation of Balanced Occupation Concept Within the Framework of Government Regulation in Lieu of Law of the Republic of Indonesia Number 02 of 2022 Concerning Job Creation - Benny Djaja; Kevin Hoo Kurniawan (Faculty of Law, Universitas Pekalongan, 2023)
By issuing it and displaying regulations related to the concept of balanced housing, the criteria for implementing balanced development have also changed. The publication of the Perppu Ciptaker and its derivative regulations, namely PP No. 12 of 2021 relating to implementation and residential areas, provides another alternative for developers who cannot construct simple houses or flats with conversions in the form of funds for the construction of public houses. The research method to be used is the normative juridical qualitative method. A new alternative for developers is regulated through Perppu Ciptaker, namely, payment of conversion funds for the construction of public houses. Housing with balanced housing is built utilizing conversion funds as an alternative to the requirement to build subsidized simple housing. These funds can be managed or come in the form of grants from development actors. A fee is assessed to the Agency for the Acceleration of Housing Implementation (AHIC) for the conversion (BP3). To speed up the delivery of inexpensive public housing for working class individuals, the federal government established BP3. Land is provided, simple houses and public flats are built, infrastructure, services, and public utilities are developed, and housing is managed and invested using the money BP3 receives